2019
DOI: 10.1371/journal.pone.0219689
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in HIV/AIDS mortality in China from 1990 to 2016: Gender disparities

Abstract: Objectives HIV/AIDS has become the leading cause of death by infectious disease in China since 2009. However, the trend of gender disparities in HIV/AIDS has not been reported in China since 1990. Our study aimed to explore the secular trend of HIV/AIDS mortality in China from 1990 to 2016 and to identify its gender disparities over the past 27 years. Method The mortality data of HIV/AIDS were obtained from the Global Burden of Disease Study 2016 (GBD 2016). Logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
3
32
0
1
Order By: Relevance
“…The period effect showed that the incidence of HIV/AIDS in males was consistently higher than that in females during the study period, and the rate of increase in males was signi cantly higher than in females, which is consistent with the results of other studies [33][34]. The incidence among immigrant males was the highest, rising sharply from 2008 to 2010, then leveling off from 2010 to 2012 (7-8 per 100,000 population) and rising sharply again from 2012 to 2017 (16-17 per 100,000 population).…”
Section: Discussionsupporting
confidence: 91%
“…The period effect showed that the incidence of HIV/AIDS in males was consistently higher than that in females during the study period, and the rate of increase in males was signi cantly higher than in females, which is consistent with the results of other studies [33][34]. The incidence among immigrant males was the highest, rising sharply from 2008 to 2010, then leveling off from 2010 to 2012 (7-8 per 100,000 population) and rising sharply again from 2012 to 2017 (16-17 per 100,000 population).…”
Section: Discussionsupporting
confidence: 91%
“…Previous research in China has shown multiple factors contributing to this rise in HIV/AIDS related mortality. In particular, late diagnosis, education level, socioeconomic status, and older age were also associated with AIDS-related mortality (54). Thus, earlier diagnosis and immediate ART initiation are strategies that could be strengthened to reduce this burden of HIV-related deaths.…”
Section: Hiv/aids Compared To Other Infectious Diseasesmentioning
confidence: 99%
“…Firstly, Changes of the demographic characters aggravated this issue. According to a Chinese census [23], the sex ratios of male to female at birth rose since 1990.The same concern existed in the U.S. as well. More HIV infections among males eventually lead a larger gender gap in HIV/AIDS incidence.…”
Section: Discussionmentioning
confidence: 96%
“…Nevertheless, advanced therapies on patients after HIV infection just restricted it spreading but can't eliminate the virus completely [43], uncontrollable high risk behaviors under its culture background [44] may cause HIV resurgence. At the same time, the advent of some aggressive treatment regimens accompanied with side-effects too [45]. Suffering sever side-effect pro les made potential patients hesitate to receive therapies or not and eventually resulted more new infections continued to occur.…”
Section: Discussionmentioning
confidence: 99%